2007
DOI: 10.1016/j.biomaterials.2007.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of nanoporous alumina membranes for immunoisolation

Abstract: Cellular immunoisolation using semi-permeable barriers has been investigated over the past several decades as a promising treatment approach for diseases such as Parkinson's, Alzheimer's, and Type 1 diabetes. Typically, polymeric membranes are used for immunoisolation applications; however, recent advances in technology have led to the development of more robust membranes that are able to more completely meet the requirements for a successful immunoisolation device, including well controlled pore size, chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(110 citation statements)
references
References 39 publications
1
108
0
1
Order By: Relevance
“…37,40,56 The second approach allows for considerably better control of the thickness and functionality of the formed coatings.…”
Section: Considerations In the Strategy For Surface Derivatizationmentioning
confidence: 99%
See 1 more Smart Citation
“…37,40,56 The second approach allows for considerably better control of the thickness and functionality of the formed coatings.…”
Section: Considerations In the Strategy For Surface Derivatizationmentioning
confidence: 99%
“…3,37,40,43,48,67 PEGylated surfaces demonstrate some of the highest protein resistance; they are relatively durable; and chemically, PEGs are relatively easy to manipulate. 40,52,58 Utilizing self-assembled monolayers (SAMs) of alkylthiols on gold surfaces for engineering of bioactive interfaces has gained significant popularity due to the simplicity of the used chemistry 45,74 and to the availability of high-resolution structural information for such SAMs. 80 Furthermore, engineering of bioactive interfaces over thin metal films has been a driving force for the development of biosensing applications based on surface plasmon resonance techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies related to the effect of nanotopography on cellular behavior indicated that osteoblast adhesion and functionality was enhanced by 30% when cultured on a nanograined Al 2 O 3 and TiO 2 substrate (4-6) compared with those cultured on a micrograined surface, and nanostructures such as TiO 2 nanotubes with Ͻ100-nm spacing showed superior characteristics in bone mineral synthesis (5). However, most of the previous studies on nanostructures and cell responses have mainly used oriented, patterned, or semiordered polymer arrays (7)(8)(9) and alumina/ polymer hybrid patterned arrays (10).…”
mentioning
confidence: 99%
“…Metallic films, with their distinct opacity toward visible light and adequate bandwidth across the entire visible spectrum, afford a better alternative. In this work, low-cost titanium and aluminum (with oxidized layer) were chosen for their biocompatible properties [29][30][31][32].…”
Section: Optical Characteristics Of Reaction Slidesmentioning
confidence: 99%